PINOID‐centered genetic interactions mediate auxin action in cotyledon formation - Wei Zeng; Xiutao Wang; Mengyuan Li (Plant Direct)
Abstract Auxin plays a key role in plant growth and development through auxin local synthesis, polar transport, and auxin signaling. Many previous reports on Arabidopsis have found that various types of auxin‐related genes are involved in the development of the cotyledon, including the number, symmetry, and morphology of the cotyledon. However, the molecular mechanism by which auxin is involved in cotyledon formation remains to be elucidated. PID, which encodes a serine/threonine kinase localized to the plasma membrane, has been found to phosphorylate the PIN1 protein and regulate its polar distribution in the cell. The loss of function of pid resulted in an abnormal number of cotyledons and defects in inflorescence. It was interesting that the pid mutant interacted synergistically with various types of mutant to generate the severe developmental defect without cotyledon. PID and these genes were indicated to be strongly correlated with cotyledon formation. In this review, PID‐centered genetic interactions, related gene functions, and corresponding possible pathways are discussed, providing a perspective that PID and its co‐regulators control cotyledon formation through multiple pathways.